We have been harmonized : life in China's surveillance state - Strittmatter, Kai (Custom House, 2020)
Hailed as a masterwork of reporting and analysis, and based on decades of research within China, We Have Been Harmonized, by award-winning correspondent Kai Strittmatter, offers a groundbreaking look at how the internet and high tech have allowed China to create the largest and most effective surveillance state in history. We Have Been Harmonized is a terrifying portrait of life under unprecedented government surveillance--and a dire warning about what could happen anywhere under the pretense of national security.